Novel homozygous DEAF1 variant suspected in causing white matter disease, intellectual disability, and microcephaly. Issue 6 (25th March 2014) - Faqeih, Eissa A.; Al‐Owain, Mohammed; Colak, Dilek; Kenana, Rosan; Al‐Yafee, Yusra; Al‐Dosary, Mazhor; Al‐Saman, Abdulaziz; Albalawi, Fadwa; Al‐Sarar, Dalia; Domiaty, Dalia; Daghestani, Maha; Kaya, Namik
<x xml:space="preserve">Abstract</x> DEAF1 encodes a transcriptional binding factor and is a regulator of serotonin receptor 1A. Its protein has a significant expression in the neurons of different brain regions and is involved in early embryonic development. In addition, its role in neural tube development is evident from the knockout mouse as many homozygotes have exencephaly. Heterozygous mutations of this gene have been linked to intellectual disability in addition to the gene's involvement in major depression, suicidal tendencies, and panic disorder. In this clinical report, we describe two children from a consanguineous family with intellectual disability, microcephaly, and hypotonia. The brain MRI of both patients showed bilateral and symmetrical white matter abnormalities, and one of the patients had a seizure disorder. Using whole exome sequencing combined with homozygosity mapping, a homozygous p.R226W (c.676C>T) mutation in DEAF1 was found in both patients. Furthermore, sequencing analysis confirmed complete segregation in tested family members and absence of the mutation in control cohort (n = 650). The mutation is located in a highly conserved structural domain that mediates DNA binding and therefore regulates transcriptional activity of its target molecules. This study indicates, for the first time to our knowledge, a hereditary role of DEAF1 in white matter abnormalities, microcephaly and syndromic intellectual disability. © 2014 Wiley Periodicals, Inc.